Contamination as a cause of abnormal inflexion class changes in ‘Alpine’ Romance, and what it tells us about word-structure - Maiden, M (Oxford University Press, 2024)
This study explores some anomalies in the history of ‘conjugations’ (inflexion classes in verbs) in the Romance languages, and particularly in Ladin dialects, with some other varieties of the Alpine area. At issue is a small, generally closed and unproductive, class which I label the ‘second/third’ conjugation, and a considerably smaller subclass within the ‘second/third’ conjugation labelled simply the ‘second conjugation’. Completely ‘against the grain’ of Romance conjugation-class changes, certain verbs, of ‘modal’ or ‘meteorological’ meaning, not only unexpectedly enter the ‘second/third’ conjugation but even penetrate its inner sanctum, the second conjugation. I claim that these anomalous developments are the result of associative interference between semantically similar lexemes (‘contamination’) and that they throw particular light on the fluid nature of the relation between the expression of lexical meaning and internal morphological structure in inflexional word-forms.